PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MAHASISWA TINGKAT II PROGRAM STUDI PENDIDIKAN BAHASA JEPANG FKIP UNRI - oktaviah, Jamalia; Hadriana, Hadriana; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study discusses about the motivation of learning towards the second grade students of Japanese Language Education Studies Program FKIP UNRI.The purpose of the authors in conducting this research to know the great influence of learning motivation on student learning outcomes.Respondents in this study amounted to 30 students of Japanese Language Education Studies Program FKIP UNRI.This research uses descriptive quantitative method.The results of this study hypothesis test using linear regression technique obtained correlation coefficient of 0.00 and F 6.23 with p = 0.000, therefore it means p> 0.01 then it can be interpreted the hypothesis in this study accepted.From the results obtained motivation to learn is in the category enough with the value, the value of coefficient received (R2) of 3,88% indicates changes in learning outcomes are influenced between mood, the ability means that the variables and results of student learning outcomesKeywords: Motivation , Learning Result